Integrated-optics pressure sensor with improved range and sensitivity based on a SiO2 arrayed waveguide grating (AWG) and a 3D printed stereolithography resin module. (October 2021) - Yin, Rui; Huang, Qingjie; Yang, Hongliang; Lu, Lin; Cao, Lingxin; Ji, Wei; Jiang, Shouzhen; Luo, Yanxia; Liu, Fengyu; Sun, Jingwen; Yin, Xiaojie; Su, Xiaohua
Highlights: SiO2 AWG combined with 3D printed stereolithography resin module using quasi self-assembling technology. Large range pressure sensor (up to 80 MPa) using integrated optics technology. The sensitivity is improved by 9 times. Resolution for water depth sensing: 0.059 m (0.0007% FS) Abstract: An integrated optical pressure sensor based on a SiO2 arrayed waveguide grating (AWG) and a phase amplifying pressure block (PAPB) 3D-printed with stereolithography resin is described in this paper. Theoretical analysis of the AWG shows that its sensitivity can be improved by applying pressure on the PAPB instead of the whole chip. This scheme is shown to be feasible by mechanical simulation of a 1 mm-thick SiO2 chip. We use the standard planar lightwave circuit (PLC) process to fabricate a SiO2 AWG and 3D print the PAPB using stereolithography resin SOMOS Imagine 8000. Adding the PAPB module to the AWG chip improves the sensitivity of the sensor by 9 times, and the measuring range reaches 80 MPa. The resolution of the device reaches 0.0007% FS (full scale).